Efeito da somatotropina bovina (bST na concentração hormonal e subsequente desenvolvimento folicular em vacas sincronizadas - MACIEL, Joyce Patu de Oliveira (2016)
Folliculogenesis, can be defined by the process involves follicular development since the activation steps, growth and maturation being controlled by a complex interplay between endocrine factors, paracrine and autocrine. Among the factors involved in the regulation of folliculogenesis, can highlight the growth hormone (GH) and growth factor similar to insulin (IGF-I), which are important regulators of the various stages of follicular development. They included 30 cows of Angus randomly divided according to age and body condition score. The animals were separated into two groups of 15 animals and subjected to a pre-synchronization protocol followed by a synchronization protocol 7d CO-Synch + CIDR. One group received a dose of 500mg bST d-0 of the synchronization protocol. Blood samples and ultrasound ovaries were performed d-d-0 to 11. Follicular diameter of variables, hormone concentration of estrogen, progesterone and IGF-I were used as evaluation criteria. Treatment with bST presented significant differences p< 0.01 for IGF-I, however other variárias not suffered significant influence. In sumary the bovine somatotropin increase the concentration of IGF-I.